2009
DOI: 10.1001/archsurg.2009.80
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Tumors of the Ampulla of Vater

Abstract: This is one of the largest series of neuroendocrine tumors of the ampulla. Preoperative biopsy was accurate, but computed tomographic scans were insensitive in detecting nodal metastases. Unlike duodenal carcinoid tumors, hypersecretion syndromes were absent and small tumor size did not preclude locoregional metastases. Tumor grade predicted survival. We recommend pancreaticoduodenectomy for this disease, with local resection reserved for mobile, superficial lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 15 publications
2
30
1
Order By: Relevance
“…Third, all the included NAD-NETs in our present study were ≤20 mm in diameter. Most of the previous studies on D-NETs included those of >20 mm in diameter or ampullary D-NETs [8,10,11,12,14,16,17,18,19], the latter having a growth pattern different from that of NAD-NET [7,8,9,10]. For example, Burke et al [10] reported the pathological finding of 99 D-NETs but 42 of them were >20 mm in diameter and included ampullary tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, all the included NAD-NETs in our present study were ≤20 mm in diameter. Most of the previous studies on D-NETs included those of >20 mm in diameter or ampullary D-NETs [8,10,11,12,14,16,17,18,19], the latter having a growth pattern different from that of NAD-NET [7,8,9,10]. For example, Burke et al [10] reported the pathological finding of 99 D-NETs but 42 of them were >20 mm in diameter and included ampullary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is generally recommended for ampullary D-NET regardless of the tumor size due to its anatomical location and more aggressive behavior compared to the latter type [7,8,9,10]. On the other hand, the therapeutic approach in NAD-NET depends on the size of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only approximately 120 NETAoVs have been described in the literature, most in less 10 cases reports [15]. The incidence and prevalence of neuroendocrine tumor seems to have increased in recent years, most likely due to diagnostic technical improvements and endoscopic healthcare surveillance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Less frequently, gastrointestinal bleeding or pancreatitis (6%) may be present. Weight loss has been seen in 4% -10% of patients at the time of presentation [5] [9]. ANET have been found to occur with higher frequency in patients with neurofibromatosis type 1 and multiple endocrine neoplasia type 1 syndrome, along with other rare cancers such as gastrointestinal stromal cell tumors and periampullary carcinomas.…”
Section: Presenting Symptoms and Diagnosismentioning
confidence: 99%
“…Since tumor size has not been clearly established to correlate with lymph nodal positivity status, pancreaticoduodenectomy is often recommended as the treatment of choice for tumors of any size with no distant spread [9] [12] [13]. However, less invasive procedures like local excision and endoscopic resections have also been successfully attempted, especially for ANET less than 2 cm size or in high risk surgical candidates [4] [5] [14].…”
Section: Therapeutic Optionsmentioning
confidence: 99%